Frequency and Factors Associated with Hyperglycaemia First Detected during Pregnancy at Itojo General Hospital, South Western Uganda: A Cross-Sectional Study - Frank Kiiza; Daniel Kayibanda; Pidson Tumushabe; Leticia Kyohairwe; Raymond Atwine; Rogers Kajabwangu; Ritah Kiconco (Journal of Diabetes Research)
Background. Hyperglycemia in pregnancy complicates up to 30% of pregnancies in Africa, and this poses a major risk to both the mother and fetus. Although recommended by the World Health Organization (WHO), universal screening for hyperglycaemia in pregnancy is not routinely done in many of the hospital in low- and middle-income countries. This study sought to determine the frequency and factors associated with hyperglycaemia first detected in pregnancy at a general public hospital in South Western Uganda. Methods. We conducted this study at Itojo General Hospital (IGH) in Ntungamo District, South Western Uganda. The study followed a cross-sectional design that employed a systematic random sampling technique to identify potential study participants during the months of October to December 2019. Using a pretested questionnaire, data on sociodemographic and medical characteristics were collected on a sample of 307 pregnant women. Blood samples were collected and analyzed for hyperglycemia using random blood sugar and fasting blood sugar test results. Data generated were analyzed with appropriate statistical tests using the statistical package for social sciences (SPSS) version 26 (SPSS Inc., USA) at P<0.05. Results. The frequency of hyperglycaemia was found to be 15.6% among the study population. Multivariate analysis revealed that the ages of 19-30 years, peasantry, and multiparity with more than 5 live children and second trimester pregnancy were independent risk factors for the observed hyperglycaemia frequency. Conclusion. Our study reports new epidemiological information about the frequency and risk factors of hyperglycaemia in pregnancy from a selected Ugandan population. Our findings suggest an introduction of hyperglycaemia screening in the routine antenatal care package for proper maternal and neonatal health outcomes.